Household income expectations: The role of unexpected income changes and aggregate conditions - Alessandro Bucciol; Joshy Z. Easaw; Serena Trucchi (Masaryk University, Faculty of Economics and Administration, 2025)
We analyse how unexpected income changes and aggregate conditions influence income expectations, their uncertainty, and expectation errors. We use a uniquely rich longitudinal Dutch survey collecting detailed information on the distribution of household income expectations. Our results show that unexpected income changes, much more than aggregate conditions, induce a revision in income expectations across the entire spectrum of the expected income distribution, consistent with extrapolative behaviour. We also document that unexpected income changes increase the uncertainty about future income. Our results provide some evidence of over-reaction, particularly to negative unexpected income changes and among high-income individuals. These effects differ based on an individual's position in the income distribution, which may be attributed to differences in income dynamics, role of insurance mechanisms, and varying levels of awareness about how unexpected income changes and aggregate conditions impact household finances.
Keywords: D84; G50; 330; Income expectations; Expectation uncertainty; Expectation error; unexpected income changes; Aggregate conditions